Pengembangan Buku Keanekaragaman Jamur Makroskopis Berbasis Literasi Sains untuk Meningkatkan Berpikir Kritis pada Mahasiswa Pendidikan Biologi UNIMED - Fathur Rahmi; Hasruddin Hasruddin; Ashar Hasairin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a science-based learning resource on the diversity of macroscopic fungi that can enhance the critical thinking skills of students in the Biology Education Program at FMIPA UNIMED. The research method used is development research employing the ADDIE model, which consists of five phases: analysis, design, development, implementation, and evaluation. The validation results from subject matter experts, instructional design experts, and layout design experts indicate that the developed textbook is highly suitable for use, with an average rating of 94.2%. The trial in the experimental class shows a significant improvement in student learning outcomes, with the average post-test score rising from 70.50 to 92.10. Based on these results, it can be concluded that the developed textbook is effective in improving students' understanding and critical thinking skills. Keywords: Critical Thinking, Science-Based Textbook, Diversity of Fungi, Development Research, ADDIE Model